Strava - projev kulturní identity řecké skupiny v Praze - Čermáková, Klára (Lidé města, 1999)
The Greek community in Prague was established by members of political emigration who arrived in Czechoslovakia between 1948 and 1949. In those years Czechoslovakia was accepting children as well as adult people evacuated from the places afflicted by a civil war. In the first years there was only a handful of Greeks, mainly officials who were in charge of contact between the Greeks living outside Prague and the Czechoslovak authorities. They were gradually joined by others who were coming to Prague through a natural process of migration from smaller towns and villages. At present the Greek community in Prague is composed of four generations of Greek immigrants and their descendants: those who arrived as adults in Czechoslovakia; children who spent their childhood in children's homes and their equals in age; their children; and now also their grandchildren. In connection with political changes in the Czech Republic, the Greek community in Prague has been strengthened by Greek students and businessmen since the early 1990s. According to the latest census, taken in 1991, there were 268 people of Greek origin in Prague. Pecularities of their diet and food habits are among cultural signs with which present-day Prague Greks are building up their identity. The writer observes the structure of the food, the way of its preparation as well as dietary habits of the families belonging to the Greek community in Prague. She compares the habits in Greek and Czech-Greek families. She asks the questions of the transmission, modification and innovation of tradition. The question of the importance of Greek food in social and family, ceremonial, events as a selfidentifying event is a vital aspect. Although Prague Greeks' favourite food has been joined by dishes from the Czech as well as other world cuisines, Greek meals have maintained their indispensable place in the diet of festive, ceremonial as well as every-day occasions. Food of the Greek cuisine is perceived as a sign of Greek identity and origin also in ethnically mixed families. The fact whether the housewife is a Greek or Czech woman only has an impact on the frequency of the preparation of the food. However, they remain part of the tradition of families with Greek origin in either cases.